Ecocene design economies: Three ecologies of systems transitions - Joanna Boehnert (2019)
Despite accumulative social and technological innovation, the design industry continues to face significant obstacles when addressing issues of sustainability. Climate change and other systemic ecological problems demands shifts on an order of magnitude well beyond the trajectory of business-as-usual. I will argue that these complex problems require addressing the epistemological error in knowledge systems reproducing unsustainable designed worlds. Ecological literacy is a basis for nature-inspired design. Ecologically engaged knowledge must inform design strategies across the psychological, the social and the environmental domains. With the expansive three ecologies perspective, interventions at the intersection of design and economics can enable systems transitions. This theoretical work informs a framing of the current epoch in ways that create a foundation for the creation of regenerative, distributed and redirected design economies.